Catheter ablation for atrial tachycardia in pediatric patients: a single-center experience - Chen, Ruoyu; Xu, Xin; He, Shuang; Liu, Qian; Liu, Lin; Zhang, Qin; Lu, Tiewei (Frontiers in Cardiovascular Medicine, 2024)
PurposeAtrial tachycardia is an uncommon supraventricular tachycardia in children. It is often drug-resistant and likely to occur concomitantly with tachycardia-induced cardiomyopathy, making radiofrequency catheter ablation the preferred treatment. The aim of this study was to assess the feasibility, safety, and effectiveness of radiofrequency catheter ablation for the treatment of different types of atrial tachycardia in children, particularly in those with drug-resistant and tachycardia-induced cardiomyopathy.MethodsA total of 28 children with atrial tachycardia (including focal atrial tachycardia and atrial flutter) who underwent atrial radiofrequency ablation at the Children's Hospital Affiliated to Chongqing Medical University from May 2018 to December 2023 were included. The baseline characteristics, preoperative medication, surgical information, and postoperative follow-up data of these children were analyzed statistically.ResultsThe mean age patients at ablation was 10.24 ± 3.40 years. A total of 78.6% of the patients (22/28) who received preoperative pharmacological treatment had intermittent or persistent atrial tachycardia. Of the 28 children who underwent radiofrequency ablation, 24 (85.7%) were diagnosed with focal atrial tachycardia, three (10.7%) with atrial flutter, and one (3.6%) with both. No postoperative complications occurred in any patient. The immediate ablation success rate in the 25 patients with focal atrial tachycardia was 96.0% (24/25). After 26.89 ± 18.17 months of follow-up, only three patients had recurrence. The ablation difficulty of focal atrial tachycardia originating in the appendage was higher than that originating in the non-atrial appendage (44.4% vs. 6.3%, p = 0.01). The success rate of ablation for atrial flutter was 100%, except in one child with underlying cardiomyopathy who experienced recurrence. Final success was achieved in 25 of the 28 patients (89.2%) at the end of the follow-up period. In addition, eight children (28.6%) in this study were diagnosed with tachycardia-induced cardiomyopathy, with significantly increased ejection fraction and shortening rate after radiofrequency ablation (p < 0.01), whereas the left ventricular end-systolic diameter were not significantly reduced during the follow-up period (p > 0.05).ConclusionRadiofrequency catheter ablation is safe and effective for the treatment of atrial tachycardia in children in the short- and long-term.It can be used as the first treatment option for children with medically refractory atrial tachycardia and tachycardia-induced cardiomyopathy.